The Safety Culture As the Basis of the Digital Society - Vasilenko, V.I.; Kornilovich, V.A. (KnE Social Sciences, 2021)
This article discusses the contradictions that emerge in global digital communication in a democracy and cultural diversity. The purpose of the study is to determine the dependence of a person’s goals on his her values in the dialogue of cultures and ways to solve the contradictions of intercultural communication. The social system does not only respond to the rapidly occurring social changes, but also respond to making political decisions. Russian scientist S.P. Kurdyumov expressed the idea that there are rules of the ban, the laws that limit the development. ’Safety Culture’ can be considered as the preservation and development of the ideals, values, norms and traditions of the individual, the family and society, social institutions and network. This study considers ’Safety Culture’ as value foundation for the digital society. This should be at the heart of every management decision referring to the digital future of our planet. A safety culture based on knowledge and observance of the ’prohibition rules’, the rules of behavior of people in global network communications will ensure the integrity of the world. Keywords: ‘Safety Culture’, digital society, values, dialogue of cultures